Internet use Patterns in the Utilization of Herbal Medicine for Chronic Diseases in Denpasar City - Suryaningsih, Ni Putu Aryati; Valencia, Valencia; Dewi, Dewa Ayu Putu Satrya; Apsari, Dewi Puspita (Indonesian Journal of Global Health Research, 2024)
The increasing use of the internet and the correctness of information causes different community knowledge about using herbal medicine for chronic diseases. This study aimed to compare knowledge levels of herbal medicine for chronic illnesses sourced on the internet. This study used a cross-sectional survey design. The number of samples used was 318. The inclusion criteria are people aged 18-60 years, know what chronic disease means (through questions in the questionnaire), and live in Denpasar City. The exclusion criteria were people who worked as health workers. Data were collected using a questionnaire and analyzed using the Kruskal-Wallis test. The results showed that most people searched using web/search sites (100%) and social media groups specifically for herbal medicine (86.5%). Knowledge of herbal medicines through web/sites and social media/chat information sources has a good understanding of 82.4% and 70.6%. Poor Knowledge of herbal medicine while using both sources of information (32.2%) and value statistics p=0.04 (p<0.05). There is a difference in the knowledge level about herbal treatments for chronic diseases between those sourced on social media and the internet. The use of the internet and social media helps people understand the content of herbal medications to treat chronic diseases.